Molecular targets of chromatin repressive mark H3K9me3 in primate progenitor cells within adult neurogenic niches - Foret, Michael R.; Sandstrom, Richard S.; Rhodes, Christopher T.; Wang, Yufeng; Berger, Mitchel S.; Lin, Chin-Hsing Annie (Frontiers in Genetics, 2014)
Histone 3 Lysine 9 (H3K9) methylation is known to be associated with pericentric heterochromatin and important in genomic stability. In this study, we show that trimethylation at H3K9 (H3K9me3) is enriched in an adult neural stem cell niche- the subventricular zone (SVZ) on the walls of the lateral ventricle in both rodent and non-human primate baboon brain. Previous studies have shown that there is significant correlation between baboon and human regarding genomic similarity and brain structure, suggesting that findings in baboon are relevant to human. To understand the function of H3K9me3 in this adult neurogenic niche, we performed genome-wide analyses using ChIP-Seq (chromatin immunoprecipitation and deep-sequencing) and RNA-Seq for in vivo SVZ cells purified from baboon brain. Through integrated analyses of ChIP-Seq and RNA-Seq, we found that H3K9me3-enriched genes associated with cellular maintenance, post-transcriptional and translational modifications, signaling pathways, and DNA replication are expressed, while genes involved in axon/neuron, hepatic stellate cell, or immune-response activation are not expressed. As neurogenesis progresses in the adult SVZ, cell fate restriction is essential to direct proper lineage commitment. Our findings highlight that H3K9me3 repression in undifferentiated SVZ cells is engaged in the maintenance of cell type integrity, implicating a role for H3K9me3 as an epigenetic mechanism to control cell fate transition within this adult germinal niche.